Modelo conceptual para la distribución de mercancías en las Nanostore pertenecientes a la zona Norte Centro Histórico de la ciudad Barranquilla (2019)
In this exploratory-descriptive research, a conceptual model is constructed for the distribution of merchandise in the traditional stores belonging to the North-Historic Center of the city of Barranquilla under the methodology of Km2, which shows all its operation in order to analyze the way stores are stocked and alternatives are suggested to improve the entire distribution. The fundamental factors of the supply process of the neighborhood stores are characterized and described, among them; demand generation, order processing, payment collection, physical distribution and after-sales service. To meet the objectives, a structured survey was applied as a data collection instrument in 139 stores located in the North-Historic Center of Barranquilla; The information collected was processed using statistical methods.